Implementasi Metode Qiro’ati Dalam Pembelajaran Baca Tulis Al-Qur’an Di Taman Pendidikan Al-Qur’an Baitul Mu’minn Benem Duduksampeyan Gresik - Aniswatun Nisa’; Amirudin, Noor; Ladamay, Man Arfa (Jurnal Mahasiswa Pendidikan, 2022)
This thesis discusses: Implementation of Al-Qur'an Reading and Writing Learning in the Qiroati Method at Baitul Mu'minin Al-Qur'an Education Park, Benem Village, Sitsampeyan District, Gresik Regency. The purpose of this study was to determine the implementation of learning to read and write the Qur'an on the qiroati method in the Baitul Mu'minin Al-Qur'an education park, Benem Village, Sitsampeyan District, Gresik Regency. And knowing the efforts and results made by Ustadzah and santri in overcoming obstacles to implementing learning to read and write the Qur'an on the Qiroati Method at the Baitul Mu'minin Al-Qur'an Education Park, Benem Village, Sitsampeyan District, Gresik Regency. This research is a qualitative research using a descriptive analysis approach, the research was carried out at the Baitul Mu'minin Benem Al-Qur'an Education Park. The data source of this study consisted of primary data, namely caregivers, ustadzah and students at the Baitul Mu'minin Benm Al-Qur'an Education Park. And secondary data is the condition of the Baitul Mu'minin Benem Al-Qur'an Education Park. While the data collection is done by using the method of observation, interviews, documentation, the collected data is then processed by data reduction techniques, data presentation, and drawing conclusions. This study found that the implementation of the Al-Qur'an Reading and Writing Learning had referred to the Qur'anic science teaching manual with the Qiroati method written by KH. Dachlan Salim Zarkasyi starting from the preparation of learning, implementation of learning to evaluation of learning